MicroRNA signatures associated with cytogenetics and prognosis in acute myeloid leukemia - Garzon, Ramiro (American Society of Hematology, 2008)
MicroRNAs (miRNAs) are small RNAs of 19 to 25 nucleotides that are negative regulators of gene expression. To determine whether miRNAs are associated with cytogenetic abnormalities and clinical features in acute myeloid leukemia (AML), we evaluated the miRNA expression of CD34(+) cells and 122 untreated adult AML cases using a microarray platform. After background subtraction and normalization using a set of housekeeping genes, data were analyzed using Significance Analysis of Microarrays. An independent set of 60 untreated AML patients was used to validate the outcome signatures using real-time polymerase chain reaction. We identified several miRNAs differentially expressed between CD34(+) normal cells and the AML samples. miRNA expression was also closely associated with selected cytogenetic and molecular abnormalities, such as t(11q23), isolated trisomy 8, and FLT3-ITD mutations. Furthermore, patients with high expression of miR-191 and miR-199a had significantly worse overall and event-free survival than AML patients with low expression (overall survival: miR-191, P = .03; and miR-199a, P = .001, Cox regression). In conclusion, miRNA expression in AML is closely associated with cytogenetics and FLT3-ITD mutations. A small subset of miRNAs is correlated with survival.